Growth of three types of sengon (Paraserianthes spp.) in varying planting spaces in agroforestry system - Frisilia Sopacua; NURHENI WIJAYANTO; DESTA WIRNAS (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Sopacua F, Wijayanto N, Wirnas D. 2021. Growth of three types of sengon (Paraserianthes spp.) in varying planting spaces in agroforestry system. Biodiversitas 22: 4423-4430. Sengon (Paraserianthes spp.) is a fast-growing tree species that is commonly cultivated in the agroforestry system by communities in Indonesia, mainly on Java Island. Among several types of sengon, Solomon sengon is currently gaining popularity due to the fast growth in height and stem diameter. Nonetheless, the spacing layout of selected sengon types is unclear, including Solomon sengon, which yields more optimal growth. This study aimed to examine the growth of three sengon types (i.e., Solomon F2, Solomon F1, and local Kendal) in three spacing patterns, namely 1.5x1.5m, 3x1.5m, and 3x3m. This research was conducted from October 2019 to January 2020 (three months) in the Cikabayan Forest, Bogor Agricultural University, Bogor, West Java. The parameters of sengon growth observed were plant height, height growth rate, stem diameter, stem diameter growth rate, tree volume, and canopy area. Data analysis was performed using ANOVA and continued with Duncan's. The results showed that all types of sengon had optimal growth in the agroforestry system at various spacings. The growth of Solomon F2 adapted well to denser spacings (1.5x1.5m and 1.5x3m) with the highest averages in plant height, stem diameter, volume, and canopy area of ??10.50 m, 8.65 cm, 0.36 m3, and 5.39 m2. Local Kendal had optimal growth at a wider spacing (3x3m) with the highest average stem diameter, volume, and canopy area of ??8.96 cm, 0.043 m3, and 1063 m2. While Solomon F1 adapted well to the three spacings with the highest average in plant height, the growth rate of plant height, stem diameter, volume, and canopy area of ??10.05 m, 1.54 m, 8.59 cm, 0.042 m2, and 2075.30 m2. In general, it can be concluded that the Solomon F1 sengon can adapt well to narrow distances or wide distances. While Solomon F2 is more recommended to be planted at a narrower distance and Kendal local sengon is more recommended to be planted at a wider distance to get optimal growth.